2021
DOI: 10.5812/jhealthscope.115575
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk Factors for Length of Hospitalization in COVID-19 Patients: A Cross-sectional Study

Abstract: Background: Identifying the potential risk factors of the length of stay in hospital (LOSH) in COVID-19 patients could help the health system meet future demand for hospital beds. Objectives: This study aimed to determine the factors affecting the length of stay in hospital in COVID-19 patients in Hamadan, the west of Iran. Methods: This cross-sectional study recruited 512 hospitalized COVID-19 patients in Hamadan city. Demographic, clinical, and medical laboratory characteristics of the patients and their sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It seems higher hospital admission rate, prolonged length of stay, and need to the specialized treatments [2][3][4] are among the most probable reasons for increased hospitalization cost among COVID-19 patients. A study in Hamadan city, Iran showed that the median lengths of hospitalization in COVID-19 patients was five days and some demographic and clinical features were related with a higher length of stay in patients [5]. Another study revealed that being more than 60 year old, respiratory rate more than 30 per minute, having comorbidity, and having a prolonged hospitalization, the risk of mortality in COVID-19 Increased [6].…”
Section: Open Accessmentioning
confidence: 99%
“…It seems higher hospital admission rate, prolonged length of stay, and need to the specialized treatments [2][3][4] are among the most probable reasons for increased hospitalization cost among COVID-19 patients. A study in Hamadan city, Iran showed that the median lengths of hospitalization in COVID-19 patients was five days and some demographic and clinical features were related with a higher length of stay in patients [5]. Another study revealed that being more than 60 year old, respiratory rate more than 30 per minute, having comorbidity, and having a prolonged hospitalization, the risk of mortality in COVID-19 Increased [6].…”
Section: Open Accessmentioning
confidence: 99%